Enhanced accumulation of phenolics in pea (Pisum sativum L.) seeds upon foliar application of selenate or zinc oxide - Malka, Maksymilian; Du Laing, Gijs; Kurešová, Gabriela; Hegedüsová, Alžbeta; Bohn, Torsten (Frontiers in Nutrition, 2023)
Selenium (Se) and zinc (Zn) are essential antioxidant enzyme cofactors. Foliar Se/Zn application is a highly effective method of plant biofortification. However, little is known on the effect of such applications on the concentration of trace elements and phytochemicals with pro- or antioxidant activity in pea (Pisum sativum L.). A 2-year pot-experiment (2014/2015) was conducted to examine the response of two pea varieties (Ambassador, Premium) to foliar administered sodium selenate (0/50/100g Se/ha) and zinc oxide (0/375/750g Zn/ha) at the stage of flowering. Concentrations of selected trace elements (Fe, Cu, Mn), total phenolic content (TPC), total flavonoid content (TFC), and total antioxidant activity (ABTS, FRAP) of seeds were determined. Se/Zn treatments did not improve concentration of trace elements, while they generally enhanced TPC. Among examined treatments, highest TPC was found in Ambassador (from 2014) treated with 100g Se/ha and 750g Zn/ha (2926 and 3221 mg/100g DW, respectively) vs. the control (1737 mg/100g DW). Additionally, 50g Se/ha increased TFC vs. the control (261 vs. 151 mg/100g DW) in Premium (from 2014), 750g Zn/ha increased ABTS vs. the control (25.2 vs. 59.5 mg/100g DW) in Ambassador (from 2015) and 50g Se/ha increased FRAP vs. the control (26.6 vs. 18.0 mmol/100g DW) in Ambassador (from 2015). In linear multivariable regression models, Zn, Mn, Cu and TPC best explained ABTS (R = 0.577), while Se, Cu and TPC best explained FRAP findings (R = 0.696). This study highlights the potential of foliar biofortification with trace elements for producing pea/pea-products rich in health-beneficial bioactive plant metabolites.